Metformin exerts cardioprotection via attenuating mitochondrial fission in cardiac ischaemia-reperfusion injury in rats. (25th November 2020) - Palee, S; Higgins, L; Leech, T; Chattipakorn, S.C; Chattipakorn, N
Abstract: Background: Cardiac ischemia/reperfusion (I/R) injury following myocardial infarction reperfusion therapy is a phenomenon that results in further cardiomyocytes death and impaired cardiac contractility. Although metformin has been shown to exert cardioprotection in addition to glycemic control, its effect on cardiac I/R injury are still controversy, and the comparative doses of metformin in cardiac I/R injury have never been investigated. Purpose: We hypothesized that metformin given acutely prior to cardiac ischaemia exerts cardioprotection in rats with cardiac I/R injury via attenuating cardiac mitochondrial dysfunction, leading to improved left ventricular (LV) function. Methods: Forty Male Wistar rats were subjected to cardiac I/R injury. Four treatment groups were investigated. The first group received saline as a control group. The second to the fourth groups received metformin at 100, 200, and 400 mg/kg intravenously, respectively. During the I/R protocols, the LV function, arrhythmia score, and mortality rate were determined. At the end, the hearts were rapidly removed to determine infarct size, cardiac mitochondrial function, cardiac mitochondrial dynamics, and cardiac apoptosis. Results: Metformin 200 mg/kg exerted the highest level of cardioprotection through the attenuated incidence of arrhythmia, decreased infarct size (Fig. 1), improved cardiac mitochondrial function, and decreased mitochondrial fission (Fig. 1) and cardiac apoptotic markers, leading to improved cardiac function during I/R injury. Although Metformin at all doses effectively decreased infarct size, improved cardiac mitochondrial function and LV function, Metformin at 200 mg/kg exerted the best efficacy (Fig. 1). Conclusions: Metformin exerts cardioprotection by attenuating mitochondrial dysfunction and decreased mitochondrial fission, leading to decreased infarct size and ultimately improved LV function after acute cardiac I/R injury in rats. These findings also indicate the potential biphasic effects of metformin on infarct size which are dose-dependent. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Science and Technology Development Agency Thailand (NC), and Thailand Research Fund (SCC)